Discernible rhythm in the spatio/temporal distributions of transatlantic dust - Y. Ben-Ami; I. Koren; O. Altaratz; A. Kostinski; Y. Lehahn (Atmospheric Chemistry and Physics, 2012)
The differences in North African dust emission regions and transport routes, between the boreal winter and summer, are thoroughly documented. Here we re-examine the spatial and temporal characteristics of dust transport over the tropical and subtropical North Atlantic Ocean, using 10 yr of satellite data, in order to better characterize the different dust transport periods. We see a robust annual triplet: a discernible rhythm of "transatlantic dust weather". The proposed annual partition is composed of two heavy loading periods, associated here with a northern-route period and southern-route period, and one light-loading period, accompanied by unusually low average optical depth of dust. The two dusty periods are quite different in character: their duration, transport routes, characteristic aerosol loading and frequency of pronounced dust episodes. The southern-route period lasts ~4 months. It is characterized by a relatively steady southern positioning, low frequency of dust events, low background values and high variance in dust loading. The northern-route period lasts ~6.5 months and is associated with a steady drift northward of ~0.1 latitude day−1, reaching ~1500 km north of the southern-route. The northern period is characterized by higher frequency of dust events, higher (and variable) background and smaller variance in dust loading. It is less episodic than the southern period. Transitions between the periods are brief. Separation between the southern and northern periods is marked by northward latitudinal shift in dust transport and by moderate reduction in the overall dust loading. The second transition, between the northern and southern periods, commences with an abrupt reduction in dust loading and rapid shift southward of ~0.2 latitude day−1, and ~1300 km in total. Based on cross-correlation analyses, we attribute the observed rhythm to the contrast between the northwestern and southern Saharan dust source spatial distributions. Despite the vast difference in areas, the Bodélé Depression, located in Chad, appears to modulate transatlantic dust patterns about half the time.